MECHANISMS FOR IMPLEMENTING UNIVERSITIES' SOCIAL RESPONSIBILITY IN THE CONDITIONS OF UNIVERSITY AUTONOMY: THE EUROPEAN EXPERIENCE - Oksana Bulvinska (Borys Grinchenko Kyiv Metropolitan University, 2023)
The article is dedicated to the analysis of the universities' social responsibility in the conditions of university autonomy. It has been emphasized that social mission of higher education demands from universities the strengthening of their social responsibility before the state, society and the community for the quality of higher education provided, for promoting the country's innovative progress thanks to scientific research, for solving environmental and social problems, for forming values and developing human capital. University autonomy in organizational, financial, personnel and academic dimensions enables each higher education institution to choose a mechanism for implementing social responsibility in accordance with its mission, values and the model - either research or entrepreneurial. The article analyzes the experience of the University of Tartu and the University of Luxembourg. It has been found out that the mechanisms for implementing social responsibility differ depending on the model of the university. The research University of Luxembourg collaborates with private companies, municipalities, the public sector by introducing professorships based on scholarships funded by an external partner and carrying out research commissioned by an external stakeholder. The entrepreneurial University of Tartu realizes social responsibility by maximally commercializing the results of scientific research and startups of teachers, scientists and students. In such cooperation, universities use the possibilities of institutional autonomy: the opportunity to create structural divisions for cooperation with business and the community, for conducting scientific research; to use financial contributions from various donors, to receive income from the transfer of intellectual property rights; to choose areas of scientific research, to determine independently the content of educational programs and individual educational modules, etc.